2012
DOI: 10.1126/science.1226762
|View full text |Cite
|
Sign up to set email alerts
|

Electrically, Chemically, and Photonically Powered Torsional and Tensile Actuation of Hybrid Carbon Nanotube Yarn Muscles

Abstract: Artificial muscles are of practical interest, but few types have been commercially exploited. Typical problems include slow response, low strain and force generation, short cycle life, use of electrolytes, and low energy efficiency. We have designed guest-filled, twist-spun carbon nanotube yarns as electrolyte-free muscles that provide fast, high-force, large-stroke torsional and tensile actuation. More than a million torsional and tensile actuation cycles are demonstrated, wherein a muscle spins a rotor at an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
620
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 637 publications
(659 citation statements)
references
References 32 publications
16
620
1
3
Order By: Relevance
“…Fig. 6e, the response time is estimated about 0.5 s. The fiber shows a repeatable generation of the actuation stress with fast rates of 40 MPa s 1 , a value that is comparable to the peak capacity of natural and other artificial muscles (30 MPa s 1 ); 20,58 and an actuation mechanism similar to that of PEDOT/PSS films or papers in humid air. 11,13 When an electrical field is applied to the sample, electrical energy is converted to thermal energy, causing temperature to increase on the fiber (Fig.…”
Section: Electromechanical Responsementioning
confidence: 76%
See 1 more Smart Citation
“…Fig. 6e, the response time is estimated about 0.5 s. The fiber shows a repeatable generation of the actuation stress with fast rates of 40 MPa s 1 , a value that is comparable to the peak capacity of natural and other artificial muscles (30 MPa s 1 ); 20,58 and an actuation mechanism similar to that of PEDOT/PSS films or papers in humid air. 11,13 When an electrical field is applied to the sample, electrical energy is converted to thermal energy, causing temperature to increase on the fiber (Fig.…”
Section: Electromechanical Responsementioning
confidence: 76%
“…Although it has been shown that short-time application of high voltages does not harm the polymer, long term operation results in electrical failure of the materials. 20 Small size microactuators should also feature enhanced response rate and be powered with coin batteries. 3 In addition, increasing the conductivity of the material can improve response rate and permit the use at low voltage power sources.…”
Section: Introductionmentioning
confidence: 99%
“…Systems are further classified by colour in terms of the mechanism of their activation and include chemical (red) and electrical (blue) active mechanisms, as well as hygroscopic (green) and thermal (yellow) passive mechanisms. The specific systems included in this figure (abbreviations used in the figure are shown in parentheses) are the sea cucumber dermis 9 , venus fly trap (VFT) 69 , human muscle contraction 59 , pH-activated polymers (pH) 59 , liquid crystal elastomers (LCE) 99 , shape-memory alloys (SMAs) 63 , mimosa plant 64 , legume forisomes 62 , shape-memory polymers (SMPs) 67 , electroactive polymers (EAPs) 59 , tree branch movement 57 , seed opening 110 , carbon nanotube (CNT) muscles 65 , electrically activiated hydrogels 61,66 , coiled nylon and polyethylene (PE) muscles 60 , cardiomyocytes 68 and spider silk 58 .…”
Section: Engineering Of Biomimetic Systemsmentioning
confidence: 99%
“…Giant torsional actuation from highly twisted fibres and yarns has been recently discovered [1][2][3][4][5][6] with potential applications in microfluidic mixing [1] and digital displays [3]. Volume expansion induced thermally, chemically, photonically or electrochemically causes partial untwist of highly twisted carbon nanotube, graphene or oriented polymer fibres and yarns [1,6].…”
Section: Introductionmentioning
confidence: 99%